Time-dependent density functional theory for the freezing/melting transition in interfacial systems. (2nd November 2019) - Liu, Yu; Guo, Fangyuan; Hu, Jun; Liu, Honglai; Hu, Ying
Highlights: Establish a time-dependent density functional theory for freezing/melting transition. Predicted a serious of crystal/quasicrystal structures depending on the conditions. Obtained the free energy profile and its relationship to the break in symmetry. Give an insight into the dynamic behavior of freezing/melting in nanoscale. Abstract: We propose a three-dimensional time-dependent density functional theory (TDDFT) to investigate the freezing/melting of Lennard-Jones fluids in interfacial systems including flat interfaces and nano-droplets. The theory is based on a modified fundamental measure theory (MFMT) for the hard-sphere reference system plus mean field theory (MFT) for the attractive contributions plus an additional weighted density approximation (WDA) contribution to enforce that bulk liquid equation of state is that of modified Benedict, Webb and Rubin (MBWR). By using different initial states, our theory generated a series of equilibrium structures including crystals and polyhedral particles. The non-linear effect and the irreversibility of the freezing/melting process were captured. The profiles for free energy and the order parameter indicate that the free energy barrier existing in the freezing/melting process is caused by the break in symmetry. Additionally, the time-dependent properties were also examined, and provided insight into the mechanism of the freezing process.